2018
DOI: 10.3892/or.2018.6780
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor effects of arsenic disulfide on the viability, migratory ability, apoptosis and autophagy of breast cancer cells

Abstract: In the present study, the antitumor effects of arsenic disulfide (As2S2) on the proliferative, survival and migratory ability of human breast cancer MCF-7 and MDA-MB-231 cells were investigated, and its potential underlying molecular mechanisms with an emphasis on cell cycle arrest, apoptosis induction, autophagy induction and reactive oxygen species (ROS) generation were determined. The results indicated that As2S2 significantly inhibited the viability, survival and migration of breast cancer cells in a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 66 publications
(75 reference statements)
0
15
0
Order By: Relevance
“…Autophagy is the process of transporting damaged, denatured or aging proteins, and organelles into lysosomes for digestion and degradation. Under normal physiological conditions, autophagy helps cells to maintain a self-stable state; however, during stress, autophagy prevents accumulation of toxic or carcinogenic damaged proteins and organelles, and inhibits cell carcinogenesis (1)(2)(3)(4). Once a tumor is formed, autophagy can be harmful as cells provide additional nutrients and promote tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is the process of transporting damaged, denatured or aging proteins, and organelles into lysosomes for digestion and degradation. Under normal physiological conditions, autophagy helps cells to maintain a self-stable state; however, during stress, autophagy prevents accumulation of toxic or carcinogenic damaged proteins and organelles, and inhibits cell carcinogenesis (1)(2)(3)(4). Once a tumor is formed, autophagy can be harmful as cells provide additional nutrients and promote tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…We have used autophagy inhibitors 3-MA and autophagy inducer rapamycin to study RQDs’ effect and found the effect of RQDs induced autophagy cannot be repressed by 3-MA, nor enhanced by rapamycin ( Fig. S2 ), Suggesting that RQDs may be a special autophagy inducer ( Zhao et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The study thus suggests the arsenic sulphide acts as an anti breast cancer agent by inducing apoptosis through both of its pathways i.e extrinsic and intrinsic , arrest the cell cycle at its phases, induce autophagy regulates protein expression of metalloproteinase-9 (MMP-9) and its signaling along with the production of ROS. (59) In BC Notch signaling pathway is also involved. Sibilin downregulates the overexpressed Notch-1/ERK/Akt Signaling by the use of ROS and kill the cancer cells of two breast cancer cell lines MCF7 and MDA-MB-231.…”
Section: Breast Cancermentioning
confidence: 99%